Edge Detection on Objects of Medical Image with Enhancement Multiple Morphological Gradient Method - Jufriadif Na`am (Proceeding of the Electrical Engineering Computer Science and Informatics, 2017)
Medical image is an invaluable tool in the detection of diseases or abnormalities in human organs. The low quality of medical images cause difficulty in observing the objects contained in the image, causing errors in detection. This research develops a method for improving the quality of medical images so that the edges of objects more clearly. This method is called Enhancement multiple Morphological Gradient Enhancement (EmMG). The method used at medical images had different formats, that as Computed Tomography Scan (CT-Scan) with format type Windows bitmap (bmp), Chest X-Ray with format type Joint Photographic Experts Group (jpg) and Panoramic X-Ray with format type Portable Network Graphics (png). The method developed produces images that can further clarify the edge of the object in the medical image, making it easier to detect diseases or abnormalities in the human body. This method can used as one of the solutions in medical help to improve the accuracy in detecting objects in medical images because the edge of the objects seen clearly.